Ethnic Divisions and the Size of the Informal Sector - David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper investigates the relationship between ethnic fragmentation and the size of the informal economy. Recent experimental and empirical research links, in turn, ethnicity and trust, and trust and tax compliance. In addition, recent empirical studies have identified an unwillingness to contribute to public goods benefiting other ethnic groups. Combining these insights, we argue that increasing ethnic fractionalization decreases voluntary tax compliance, and present empirical evidence at the macro level in a cross-section of more than fifty countries, that more ethnically fragmented societies have significantly larger informal sectors.
Keywords: H26; J15; O17; 330; informal sector; ethnic fragmentation; voluntary tax compliance; Informeller Sektor; Ethnische Gruppe; Steuermoral; Welt